Modification of Oligo- and Polylactides With Macrocyclic Fragments: Synthesis and Properties - Mostovaya, Olga A.; Gorbachuk, Vladimir V.; Padnya, Pavel L.; Vavilova, Alena A.; Evtugyn, Gennady A.; Stoikov, Ivan I. (Frontiers in Chemistry, 2019)
Products of lactic acid polycondensation (poly- and oligolactic acids) are widely used as packaging materials, drug delivery agents, implants etc. Variety of their applications is caused by a number of practically important properties, e.g., biocompatibility and biodegradability, non-toxicity, and mechanical durability. Modification of these polymers with different additives allows improving their properties and extending future applications. In this manner, stability toward degradation, recognition of some substrates, extended thermal stability etc. can be improved. Macrocyclic compounds are promising candidates as modifiers. They are able to provide polymer materials with additional binding sites, impart certain orientation to spatial arrangement of polymer chains, change hydrophilic-lipophilic balance and redox properties. The latter one can be used for assembling various electrochemical sensors and biosensors that combine steric discrimination of the analytes caused by oligolactides and highly sensitive response to their quantities caused by redox labels introduced. Different composite materials based on oligolactides as matrices for such redox labels were described in the assemblies of biosensors for drugs, pesticides and antioxidants detection. In this mini-review, methods for the synthesis of the lactic acid oligomers and those modified with the macrocyclic fragments (porphyrin, cyclodextrin and cyclophane) have been described. The effects of modifiers on complexation, thermal and aggregation properties of materials are described. Analytical performance of oligolactide based sensors and biosensors has been considered with particular emphasis to the mechanism of signal generation.